Разработка структурной схемы 3D-биопринтера с обратной связью - Селезнев, И. С.; Тымкович, М. Ю.; Костин, Д. А. (My University, 2019)
3D-bioprinting (or bioprinting) along with gene and cell engineering occupies one of the most leading, actively developing and promising areas of modern biomedical engineering. The importance of the development of this branch of scientific research is indisputable, as it makes it possible to restore not only tissues, but even some of the lost functions of the body with high accuracy and optimal speed. 3D bioprinting allows you to minimize the human factor of surgical error
Keywords: 3D биопринтер; связь обратная